Outpatient Service at Veterinary Clinics in Manizales (Colombia): Epidemiological Analysis in Dogs - Muñoz, Jefferson; Ramírez, Ginés Fernando; Garcés, Luisa Fernanda (Spei Domus, 2015)
Introduction: The importance of pets and their direct relationship with public health and zoonoses greatly influence the need for epidemiological databases in Colombia. Materials and methods: For eight months, information of dogs cared for at nine veterinary clinics in Manizales, Colombia was obtained. Variables such as race, sex, reproductive status, reason for consultation, clinical findings, and presumptive diagnoses were cataloged. Population was classified into four age groups: Group a (0-3 months); Group b (4-12 months); Group c (13-36 months); Group d (>37 months). Direct relationships among variables were evaluated and the existence of significant differences between groups and relevant statistical data was analyzed. Results: 2414 dogs, 1381 males (11.3% castrated), 1033 females (26% sterilized) were reported. The distribution of population in each subgroup was: Group a (10.2%); Group b (24.7%); Group c (23.6%); Group d (41.5%). A significant difference (p